Pengaruh profibiltas, leverage, dan pertumbuhan penjualan perusahaan terhadap kondisi financial distress pada perusahaan property dan real estate di bursa efek Indonesia Tahun 2014-2018 - Mega Sitanggang; Dani Handayani; Ike Rukmana Sari (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study analyzes the effect of profitability, leverage, and company sales growth on financial distress in property and real estate companies on the Indonesian stock exchange in 2014 – 2018. The research sample is 26 companies listed on the Indonesia Stock Exchange. Data were analyzed using multiple regression models. The study results found that the average value of financial distress was 2.6623, profitability was 0.0973, leverage was 0.9588, and sales growth was -1.14581. Regression model testing shows that all research variables (profitability, leverage, sales growth) do not affect financial distress